Antibody structure and function: antibody structure - Clark, Mike (Henry Stewart Talks, 2021)
The basic antibody structure, Mammalian antibody classes, Immunoglobulin subclasses, Structure of different subclasses and classes of antibody, Soluble and cell-surface antibodies